The Concept of General Meaning in Maqayis Al-lughah by Ibn Faris - Kahayev, Amir (Scholarya Demo Journal of Ruby, 2018)
According to Ibn Faris, the scholar in Arabic philology, errors are frequent in the speech when the logic of language is not understood. The purpose of Ibn Faris in writing his work is to determine the general root meaning of words. He tried to mention the most obvious expression of general meaning. Thus, the words with similar meanings can be gathered around the same expression. Maqayis al-Lughah possesses some specific features such as the independence from the method of previous dictionaries, ways of giving meaning to the roots of words and the new method in composition in the history of Arabic lexicography. In fact, despite its resemblance to a dictionary, it is a book studying semantics and etymology of words. In his work, Ibn Faris reveals his own method emphasizing the meaning of a word. He defines general root meaning of words in the first place, and then tries to collect other words derived from this root around that meaning.